Dies Process Performance Improvement Maintenance With e-DMIS Based on Iot Technology - Adi Rusdi Widya; Ikhsan Romli (Universitas Dian Nuswantoro and IndoCEISS, 2021)
Improvement between departments within the company requires a mutually supportive system so that cooperation occurs between interrelated departments. This requires effort and commitment that needs to be supported by related share holders so that the occurrence of lost time during the production process can be minimized so that the planned time runs effectively and efficiently in increasing productivity. The difficulty in supervising and controlling the production process is the reason for knowing the abnormality in the process of replacing the dies and controlling the process of replacing printing equipment or dies for the Stamping process still using a manual system and the process recording system still using paper that is prone to loss and is engineered irresponsibly . The method used to create an electronic Dies replacement monitoring system by collecting problem data, comparing manual systems with several experiments and testing tools, using IoT in the form of PLC, HDMI as a tool for online communication. The DIMS monitoring system can be used to monitor and provide initial information when there is a request for the Dies replacement process so that replacement requests and needs in the process can be carried out immediately because they can be detected early.